Utilization of Preferential Trade Arrangements: Sri Lanka's Experience with the EU and US GSP Schemes - Janaka Wijayasiri (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
The GSP scheme was initiated by UNCTAD in 1968 with the objective of enabling developing country exports to enter developed country markets under preferential rates. Sri Lanka has been a beneficiary under the GSP scheme over the last three decades. However, meeting the scheme's objective of export expansion seems to have fallen short and Sri Lanka has not been able to export effectively under the EU and US GSP schemes, which are the most important non-reciprocal preference arrangements providing access to Sri Lanka's main export markets.
Keywords: F1; 330; Generalized System of Preferences (GSP); Rules of Origin(RoO); EU; US; Sri Lanka